Association of circulating miRNAS in patients with Alstrőm and Bardet-Biedl syndromes with clinical course parameters - Zmyslowska, Agnieszka; Smyczynska, Urszula; Stanczak, Marcin; Jeziorny, Krzysztof; Szadkowska, Agnieszka; Fendler, Wojciech; Borowiec, Maciej (Frontiers in Endocrinology, 2022)
Background Patients with the rare syndromic forms of monogenic diabetes: Alström syndrome (ALMS) and Bardet-Biedl syndrome (BBS) have multiple metabolic abnormalities, including early-onset obesity, insulin resistance, lipid disorders and type 2 diabetes mellitus. The aim of this study was to determine if the expression of circulating miRNAs in patients with ALMS and BBS differs from that in healthy and obese individuals and determine if miRNA levels correlate with metabolic tests, BMI-SDS and patient age. Methods We quantified miRNA expression (Qiagen, Germany) in four groups of patients: with ALMS (n=13), with BBS (n=7), patients with obesity (n=19) and controls (n=23). Clinical parameters including lipids profile, serum creatinine, cystatin C, fasting glucose, insulin and C-peptide levels, HbA1c values and insulin resistance (HOMA-IR) were assessed in patients with ALMS and BBS. Results We observed multiple up- or downregulated miRNAs in both ALMS and BBS patients compared to obese patients and controls, but only 1 miRNA (miR-301a-3p) differed significantly and in the same direction in ALMS and BBS relative to the other groups. Similarly, 1 miRNA (miR-92b-3p) was dysregulated in the opposite directions in ALMS and BBS patients, but diverged from 2 other groups. We found eight miRNAs (miR-30a-5p, miR-92b-3p, miR-99a-5p, miR-122-5p, miR-192-5p, miR-193a-5p, miR-199a-3p and miR-205-5p) that significantly correlated with at least of the analyzed clinical variables representing an association with the course of the diseases. Conclusions Our results show for the first time that serum miRNAs can be used as available indicators of disease course in patients with ALMS and BBS syndromes.